2007
DOI: 10.1242/dev.000141
|View full text |Cite
|
Sign up to set email alerts
|

Foxa1andFoxa2regulate multiple phases of midbrain dopaminergic neuron development in a dosage-dependent manner

Abstract: The role of transcription factors in regulating the development of midbrain dopaminergic (mDA) neurons is intensively studied owing to the involvement of these neurons in diverse neurological disorders. Here we demonstrate novel roles for the forkhead/winged helix transcription factors Foxa1 and Foxa2 in the specification and differentiation of mDA neurons by analysing the phenotype of Foxa1 and Foxa2 single-and double-mutant mouse embryos. During specification, Foxa1 and Foxa2 regulate the extent of neurogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
279
1
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(304 citation statements)
references
References 40 publications
15
279
1
9
Order By: Relevance
“…When control tissues obtained from a cynomolgus embryo and an adult animal were analyzed, both showed that the substantia nigra pars compacta (SNc) was strongly positive for GIRK2 and FOXA2 and weakly positive for calbindin, while the ventral tegmental area (VTA) was weakly positive for GIRK2 and FOXA2 but strongly positive for calbindin ( Figure 1J). This distinct pattern of GIRK2/FOXA2/calbindin expression in the SNc and VTA is consistent with those reported in other species, including rodents and humans (15,28,29). We also evaluated the induction efficiency of MSC-DP cells by quantitative immunocytochemistry.…”
Section: Evaluation Of Msc-dp Cellssupporting
confidence: 87%
See 3 more Smart Citations
“…When control tissues obtained from a cynomolgus embryo and an adult animal were analyzed, both showed that the substantia nigra pars compacta (SNc) was strongly positive for GIRK2 and FOXA2 and weakly positive for calbindin, while the ventral tegmental area (VTA) was weakly positive for GIRK2 and FOXA2 but strongly positive for calbindin ( Figure 1J). This distinct pattern of GIRK2/FOXA2/calbindin expression in the SNc and VTA is consistent with those reported in other species, including rodents and humans (15,28,29). We also evaluated the induction efficiency of MSC-DP cells by quantitative immunocytochemistry.…”
Section: Evaluation Of Msc-dp Cellssupporting
confidence: 87%
“…This report further characterized the MSC-DP cells and found that they were double positive for FOXA2 and GIRK2, both specific markers of differentiated A9 dopaminergic neurons. In particular, FOXA2 was recently identified as a transcription factor required for specifying and maintaining the dopaminergic neuron phenotype (28,42) and is considered to be expressed exclusively in floor plate-derived dopaminergic neurons (43). We confirmed the coexpression of FOXA2 and GIRK2 in SNc tissue that contains A9 dopaminergic neurons but not in the VTA, which contains A10 dopaminergic neurons.…”
Section: Figuresupporting
confidence: 72%
See 2 more Smart Citations
“…However, only a few graft-derived DA axons were found to innervate the host striatum, indicating a heterogenous population of engrafted Girk-2-and TH-coexpressing DA neurons. Indeed, a subset of other neurons outside the A9 region also coexpress TH and Girk-2 (26) and the engrafted PDiPS cellderived DA neurons did not coexpress the transcription factor foxA2 that is found together with TH in most A9 midbrain DA neurons (27). Therefore, we believe the PDiPS cells have most likely been inefficiently patterned toward an A9 DA neuronal phenotype during in vitro differentiation.…”
Section: Discussionmentioning
confidence: 99%